Mortality following adolescent substance treatment: 21-year follow-up from a single clinical site - Thurstone, Christian; Etzig, Cassandra; Chen, Eileen; Seely, Hayley D.; Loh, Ryan (Frontiers in Child and Adolescent Psychiatry, 2025)
BackgroundDespite known risks of substance use, mortality following adolescent substance treatment has not been examined. Knowing which youth have greatest risk and how youth die may inform future interventions.MethodsThis retrospective chart review combined records from a single adolescent substance treatment program at an urban, safety-net health system (n = 2,957, ages 10–19 years) with a public health registry of deaths from 2003 to 2024. Records from the child mental health treatment program at the same health system (n = 4,400, ages 10–19 years) were used for comparison. The crude mortality rate per 100 person years was calculated for both samples for all 21 years. The standard mortality rate using death within one year of intake was also calculated. Finally, a logistic regression model was used to test the project hypotheses that self-identification as a person of color, no engagement in care, male sex at birth, and involvement in substance treatment would predict mortality.ResultsOverall, 92 (2.1%) adolescents in mental health treatment had a death record compared to 119 (4.0%) of adolescents in substance treatment. The crude mortality rate per 100 person years for adolescents in mental health treatment was 0.19 (CI: 0.18–0.20) compared to 0.37 (CI: 0.36–0.38) for adolescents in substance treatment. The standard mortality rate was 120 (32.7–308) for adolescents in mental health treatment compared to the standardized mortality rate of 944 (CI: 599–1,420) for adolescents in substance treatment. Accidental death, which includes overdose, was the most common cause of death in both groups. Results of the logistic regression showed male sex at birth (p = 0.0434, OR = 2.10, CI 1.06–4.53) and substance treatment (p = 0.0035, OR = 3.02, CI 1.47–6.55) as predictors of death within 5 years of treatment intake.ConclusionsAdolescents in substance treatment compared to those in mental health treatment are more likely to die within 5 years of intake. Males compared to females are also more likely to die. Interventions to prevent overdose and other causes of mortality may be indicated.